Review and Prospects for Converting Coal Plants to Nuclear Plants - Xiaoyu LI; Ye HU; Zhiying CHEN (南方能源建设)
[Objective] Coal has long occupied a dominant position in China's energy system. With the acceleration of the global climate governance process, the major economies around the world are rapidly moving towards the goal of carbon neutrality. On the other hand, in recent years, the number of newly approved and under-construction nuclear power units in China has been consistently on the rise, ranking first globally. The significant emission reduction effect of nuclear power makes the transformation from coal-fired power to nuclear power (Coal to Nuclear, C2N) expected to become a new scenario for the replacement of traditional energy. This paper analyzes the current development status of Coal to Nuclear, conducts research on the key issues regarding this transformation, explores the typical scenarios of Coal to Nuclear, looks forward to the development prospects of this transformation in China, thus providing new ideas for the large-scale transformation and utilization of coal-fired power plants in China in the future. [Method] The research methods of literature review and comparative analysis were adopted to sort out the development of C2N, and the latest progress in C2N technology and practice at home and abroad were analyzed. At the same time, combined with the comparison of relevant policy and regulatory documents of the nuclear power industry and some technical parameters of coal-fired power plants and nuclear power plants, the key issues and application scenarios of C2N were discussed. [Result] This study shows that the development of C2N is theoretically feasible, but it must be developed in coordination with other types of energy to jointly serve China's energy development strategy. In the future, based on existing research and combined with factors such as technological progress, China's medium- and long-term energy and power flow, regional economic development level, and public participation, it is necessary to differentially formulate coastal and inland C2N development strategies, and further carry out site selection and determine the construction schedule on this basis. [Conclusion] Despite facing many challenges, C2N can directly achieve capacity substitution, reduce carbon emissions from coal-fired power plants, and significantly reduce the construction cost of nuclear power, its application in China can have a variety of application scenarios, which can provide an idea for rapid carbon reduction in economically developed provinces along the eastern coast, its promotion needs to be considered in an overall manner with the overall promotion of China's "carbon peaking and carbon neutrality" Goals, energy development strategy, raw material supply security, and the retirement of coal-fired power units, and be promoted in an orderly manner from the coast to the inland, its feasibility will be enhanced with the development of nuclear power technology, especially the improvement of its inherent safety, its implementation also requires top-level policy design support, involving national economic development and industrial strategies, with a long adjustment cycle, and based on the large scale of China's coal-fired power and the construction cycle of nuclear power, its implementation process may last for decades.